A system identification-based MPPT algorithm for solar photovoltaic pumping system under partial shading conditions - Celikel, Resat; Boztas, Gullu; Aydogmus, Omur (Taylor & Francis Inc, 2022)
This paper presents a Maximum Power Point Tracking (MPPT) algorithm using system identification (SI) for solar photovoltaic (PV) pumping system under partial shading (PS) conditions. The measurement of the PV panel current was not required for the proposed MPPT algorithm. The MPPT algorithm was developed for an electric motor with a nonlinear pump load. In this study, a high-efficiency synchronous reluctance motor (SynRM) was designed as a 4-inch submersible pump motor. The system aimed to the small-scale solar photovoltaic water pumping systems. The SynRM was designed and optimized to use at low voltage levels such as solar PV panels without requiring a boost converter. Thus, the motor could be connected directly with any low voltage leveled power supply. The motor was produced 0.55 kW power with an efficiency of 86.5%. Eight PS patterns were generated to obtain four different scenarios for analyzing of the proposed algorithm. The Maximum Power Point (MPP) was determined with high accuracy for global maximum for all PS conditions using the proposed algorithm. Thus, the motor was operated at the MPP in all conditions thanks to the developed algorithm. The overall system efficiency was obtained between 72% and 82% under these conditions.
Keywords: MPPT; system identification; solar water pump; solar energy; synchronous reluctance motor